2011
DOI: 10.1136/bmj.d6333
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran etexilate versus warfarin in management of non-valvular atrial fibrillation in UK context: quantitative benefit-harm and economic analyses

Abstract: Objectives To determine the incremental net health benefits of dabigatran etexilate 110 mg and 150 mg twice daily and warfarin in patients with non-valvular atrial fibrillation and to estimate the cost effectiveness of dabigatran in the United Kingdom.Design Quantitative benefit-harm and economic analyses using a discrete event simulation model to extrapolate the findings of the RE-LY (Randomized Evaluation of Long-Term Anticoagulation Therapy) study to a lifetime horizon.Setting UK National Health Service.Pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
146
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 42 publications
3
146
1
4
Order By: Relevance
“…Furthermore, at present there is no specific antidote for patients who require an immediate reversal of their effect, but for dabigatran and apixaban antidotes are in development. Also, non-VKAs have a significantly higher cost than warfarin 11 ; however, several studies have shown that they are cost-effective not only for primary stroke prevention [12][13][14][15] but also for secondary stroke prevention. 16 Finally, non-VKAs are mainly excreted via kidneys and therefore their use should be cautious in patients with renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at present there is no specific antidote for patients who require an immediate reversal of their effect, but for dabigatran and apixaban antidotes are in development. Also, non-VKAs have a significantly higher cost than warfarin 11 ; however, several studies have shown that they are cost-effective not only for primary stroke prevention [12][13][14][15] but also for secondary stroke prevention. 16 Finally, non-VKAs are mainly excreted via kidneys and therefore their use should be cautious in patients with renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 Although INR control is a determinant of the cost-effectiveness of dabigatran in studies conducted in the United States and United Kingdom, INR management in real-world populations varies, and the time in therapeutic range for patients receiving warfarin is highly variable. [11][12][13]37 A number of studies have estimated that patients spend from 41% to 72% of their time in the recommended INR range for warfarin. [38][39][40] Clinical trials for NOACs report time in therapeutic range values within this range, and therefore, INR was not incorporated as a model parameter in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trial simulations (CTS) were used to access cost-effectiveness 19 , health economic 20 , and discrete-event 19,21 . Some studies apply CTS to help understand how different genotypes influence dosing decisions 22 .…”
Section: Resultsmentioning
confidence: 99%